NRF2-Related Epigenetic Modifications in Cardiac and Vascular Complications of Diabetes Mellitus - Wang, Jie; Xiao, Mengjie; Wang, Jie; Wang, Shudong; Zhang, Jingjing; Guo, Yuanfang; Tang, Yufeng; Gu, Junlian (Frontiers in Endocrinology, 2021)
Diabetes mellitus (DM) is a highly prevalent chronic disease that is accompanied with serious complications, especially cardiac and vascular complications. Thus, there is an urgent need to identify new strategies to treat diabetic cardiac and vascular complications. Nuclear factor erythroid 2-related factor 2 (NRF2) has been verified as a crucial target for the prevention and treatment of diabetic complications. The function of NRF2 in the treatment of diabetic complications has been widely reported, but the role of NRF2-related epigenetic modifications remains unclear. The purpose of this review is to summarize the recent advances in targeting NRF2-related epigenetic modifications in the treatment of cardiac and vascular complications associated with DM. We also discuss agonists that could potentially regulate NRF2-associated epigenetic mechanisms. This review provides a better understanding of strategies to target NRF2 to protect against DM-related cardiac and vascular complications.